2022
DOI: 10.3390/jof8030304
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Wheat Leaf Rust Control Using Chitosan Nanoparticles and Salicylic Acid

Abstract: Wheat leaf rust is one of the world’s most widespread rusts. The progress of the disease was monitored using two treatments: chitosan nanoparticles and salicylic acid (SA), as well as three application methods; spraying before or after the inoculation by 24 h, and spraying both before and after the inoculation by 24 h. Urediniospore germination was significantly different between the two treatments. Wheat plants tested for latent and incubation periods, pustule size and receptivity and infection type showed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 45 publications
3
6
0
Order By: Relevance
“…Our findings revealed an overall increase in enzymatic activities. Similar results have also been reported by the application of chitosan nanoparticles in wheat [ 52 ]. The activation of defense enzymes such as PO, SOD, CAT, phenol, and flavonoids is known to boost host tolerance under biotic stress, particularly fungal stress [ 5 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings revealed an overall increase in enzymatic activities. Similar results have also been reported by the application of chitosan nanoparticles in wheat [ 52 ]. The activation of defense enzymes such as PO, SOD, CAT, phenol, and flavonoids is known to boost host tolerance under biotic stress, particularly fungal stress [ 5 ].…”
Section: Discussionsupporting
confidence: 91%
“…ZnO NPs not only display disease suppression properties but also have the ability to increase the shelf life of vegetables and fruits [ 47 ]. ZnO NPs trigger the upregulation of potential antioxidant metabolism [ 52 ]. Our findings revealed an overall increase in enzymatic activities.…”
Section: Discussionmentioning
confidence: 99%
“…The increased antioxidant properties can enhance the fitness of seedlings and plants during post-priming germination . Similar results have also been reported by the application of chitosan NPs in wheat for the upregulation of antioxidant enzymes . Mahakham et al (2017) reported the stimulation of SOD and CAT enzymatic activity in seedlings by priming the seeds with green synthesized silver NPs .…”
Section: Resultsmentioning
confidence: 99%
“…Another study by [ 52 ] found that the application of Salicylic acid reduced stripe rust severity in wheat plants as measured by AUDPC (area under production curve). Since defense genes were activated after salicylic acid treatments compared to controls [ 53 ], it was confirmed that the application of SA in wheat can activate PR-1 and PR-2 [ 14 ]. On the other hand, another study by [ 54 ] showed that Indole acetic acid treatment at 100 µgmL −1 reduced stripe rust infection and induced rust resistance in wheat cv.…”
Section: Discussionmentioning
confidence: 99%